INVESTIGATING INFORMAL DIGITAL LEARNING OF ENGLISH (IDLE) SPEAKING PRACTICES EMERGE THE BOUNDARIES BETWEEN COUNTRIES - Rani Rahmawati; Nur Arifah Drajati; Abdul Asib (Universitas Muhammadiyah Semarang, 2019)
The aim of this paper was to investigate the influences of informal digital learning of English (IDLE) speaking practices which emerge the boundaries between countries. The researcher used questionnaire, interview, document analysis, and observation as data collection. For analyzing qualitative data, the researcher used narrative inquiry model including data collection, data transcription and reporting the narrative study. The participant were two female undergraduate students of English department in Indonesia. The result explained that IDLE speaking practices influence their self-confidence, motivation, and communication competence. This research also reveald that their language learning strategy through IDLE speaking practice widen their social and culture understanding. This new language learning strategy in informal context helps digital natives in this era to enjoy their learning.